2020
DOI: 10.3390/ijms21176113
|View full text |Cite
|
Sign up to set email alerts
|

Lipophagy and Lipolysis Status in Lipid Storage and Lipid Metabolism Diseases

Abstract: This review discusses how lipophagy and cytosolic lipolysis degrade cellular lipids, as well as how these pathway ys communicate, how they affect lipid metabolism and energy homeostasis in cells and how their dysfunction affects the pathogenesis of lipid storage and lipid metabolism diseases. Answers to these questions will likely uncover novel strategies for the treatment of aforementioned human diseases, but, above all, will avoid destructive effects of high concentrations of lipids—referred to as lipotoxici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 193 publications
0
44
0
Order By: Relevance
“…Neutral lipolysis is the process in which cytoplasmic lipases such as the key cytoplasmic lipase, adipose triglyceride lipase (ATGL), and hormone-sensitive lipase (HSL) exert the hydrolytic effect by directly attaching to the surface of lipid droplets, and serving as another capital intracellular lipid degradation mode. Together with lipophagy, lipolysis constitutes the key to the regulation of lipid droplet catabolism ( Kloska et al, 2020 ). Studies have shown that lipase-driven decomposition of lipid droplets has proved part of its process depends on autophagy.…”
Section: The Function and Molecular Mechanism Of Tfeb Regulating Lipimentioning
confidence: 99%
“…Neutral lipolysis is the process in which cytoplasmic lipases such as the key cytoplasmic lipase, adipose triglyceride lipase (ATGL), and hormone-sensitive lipase (HSL) exert the hydrolytic effect by directly attaching to the surface of lipid droplets, and serving as another capital intracellular lipid degradation mode. Together with lipophagy, lipolysis constitutes the key to the regulation of lipid droplet catabolism ( Kloska et al, 2020 ). Studies have shown that lipase-driven decomposition of lipid droplets has proved part of its process depends on autophagy.…”
Section: The Function and Molecular Mechanism Of Tfeb Regulating Lipimentioning
confidence: 99%
“…Lipid homeostasis is guaranteed by a delicate equilibrium among biosynthesis, uptake and catabolism. Kloska and colleagues [7] systematically reviewed the current knowledge on lipophagy and cytosolic lipolysis, two selective lipid catabolic processes whose activity is essential for the proper regulation of energy homeostasis in cells. The authors provide an in-depth discussion of the transcriptional modulation of these pathways by the mammalian target of rapamycin complex 1 (mTORC1) and by the transcription factor EB (TFEB).…”
mentioning
confidence: 99%
“…Secondly, both pathways occur in multiple tissues and the products are same in supplying substrates for β-oxidation and cellular biosynthesis. 90 …”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, lipolysis is implemented step by step with different enzymes, such as ATGL, hormone-sensitive lipase and monoglyceride lipase. 90 Lipophagy forms autophagosomes to wrap LDs and deliver them to lysosome for degradation. Additionally, cross-talk of lipolysis and lipophagy exists.…”
Section: Discussionmentioning
confidence: 99%